Lab-sophistication: Does repeated participation in laboratory experiments affect pro-social behaviour? - Tiziana Medda; Vittorio Pelligra; Tommaso Reggiani (Games, 2021)
Experimental social scientists working at research-intensive institutions deal inevitably with subjects who have most likely participated in previous experiments. It is an important methodological question to know whether participants that have acquired a high level of lab-sophistication show altered pro-social behavioural patterns. In this paper, we focus both on the potential effect of the subjects' lab-sophistication, and on the role of the knowledge about the level of lab-sophistication of the other participants. Our main findings show that while lab-sophistication per se does not significantly affect pro-social behaviour, for sophisticated subjects the knowledge about the counterpart's level of (un)sophistication may systematically alter their choices. This result should induce caution among experimenters about whether, in their settings, information about lab-sophistication can be inferred by the participants, due to the characteristics of the recruitment mechanisms, the management of the experimental sessions or to other contextual clues.
Keywords: D03; D83; C91; C92; 330; cooperation; experimental methodology; external validity; lab-sophistication; pro-social behaviour